Usefulness of combined use of contrast-enhanced ultrasound and TI-RADS classification for the differentiation of benign from malignant lesions of thyroid nodules. - Zhang, Yan; Zhou, Ping; Tian, Shuang-Ming; Zhao, Yong-Feng; Li, Jia-Le; Li, Lan (European Radiology, 2017)
Purpose: To study the thyroid image reporting and data system (TI-RADS) classification and the contrast-enhanced ultrasound (CEUS) enhancement pattern of thyroid nodules, and to determine whether combined use of both methods is helpful in the diagnosis of thyroid nodules.Methods: A total of 319 thyroid nodules in 246 patients were assessed with TI-RADS, CEUS and a combination of both methods. The diagnostic performance of TI-RADS, CEUS and a combination of both methods was compared.Results: The accuracy in the diagnosis of thyroid nodules was 90.3 % for TI-RADS, 90.0 % for CEUS and 96.0 % for a combination of both methods respectively. A statistically significant difference was not observed in the diagnostic accuracy of CEUS and TI-RADS (P > 0.05). However, a significant difference was observed between a combination of both methods and either alone (P < 0.01). A combination of both methods showed high sensitivity, specificity and accuracy for TI-RADS classifications of 4a and 4b thyroid nodules compared with TI-RADS alone (P < 0.01) and a statistically significant difference was not observed for thyroid nodules classified as 2, 3, and 5 (P > 0.05).Conclusions: The improved TI-RADS, when combined with CEUS, could significantly improve the diagnostic accuracy for thyroid nodules, especially for TI-RADS class-4 thyroid nodules.Key Points: • TI-RADS can be used as the primary diagnostic standard for thyroid nodules • CEUS can be used as an important complement to TI-RADS • The improved TI-RADS can significantly improve the qualitative diagnostic accuracy.